Assessment of agro-morphological and molecular diversity among Indian mustard (Brasssica juncea) genotypes - SHEKHAWAT, NEELAM; SHARMA, HEMLATA; SHEKHAWAT, RAVINDRA SINGH (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted in randomized block design with three replications during winter (rabi) season2015–16 at Instructional farm, RCA, MPUAT, Udaipur. Genetic diversity of the 10 Indian mustard [Brassica juncea(L.) Czern. & Coss] varieties was evaluated by Random Amplified Polymorphic DNA markers and morphologicalcharacters. Fifteen RAPD primers were used out of which three were amplified. These three amplified primers produced total 148 amplicons, of which 128 amplicons (86.48%) were polymorphic. The polymorphic information content value ranged from 87.50% (OPA-2) to 100% (OPA-11) with an average of 93.33%. A dendrogram based on UPGMA analysis separated 10 Indian mustard varieties in four clusters at 0.58 similarity coefficient. Genetic divergence using Mahalanobis D2 statistics was worked out and based on D2 values, the varieties were grouped into four different clusters. Cluster 1 included maximum (seven) genotypes and cluster 2, 3 and 4 had only one genotype. Maximum divergence was observed between clusters 1 and 4 followed by cluster 1 and 2. Number of siliquae per plant was the main trait contributing to this divergence followed by test weight, seed yield per plant, number of seeds per siliqua, days to 50% flowering and number of secondary branches per plant. The genotypes PM-27 and Pusa Vijay were the most diverse on the basis of UPGMA clustering analysis and genotypes PM-27 and Bio-902 were most divergent on the basis of D2 value clustering. The results obtained can be utilized in hybridization and selection for breeding programmes.